Nitrogen fertilizers and bioeconomic agriculture: Example on wheat - Mihai Berca; Valentina-Ofelia Robescu; Mircea Duică; Roxana Horoiaş (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
All the scenarios and models made up by the most titled scientists in biology, agriculture, geophysics, and human health prove that the four main resources of the existence of the biosphere are so polluted that it is a matter of time until a major collapse of human existence occurs. The problem is not that it will occur, but when it will occur, in what form and how great the losses will be. Among the many factors to be applied in agriculture in order to get food, the nitrogen fertilizers play an important part. Nitrogen fertilizer application has increased crop production by about 3-4 times, but at the same time it has reduced the content of heteropoly condensate humus by 3-4 times, especially in the countries of the Eastern Europe. Both European and world specialists have found that there is a large difference in the environmental (qualitative) behaviour between the two major fertilizers applied - ammonium nitrate and urea. The research carried out by us in the experimental field of Poroschia (Teleorman County) between 2014 and 2016 showed a significant difference in the organic and productive-qualitative behaviour in favour of the ammonium nitrate. In wheat crops, the ammonium nitrate is superior to urea, at the same applied dose, averaging 3.5-8.0 q/ha and with a protein content of 0.3-1.5%. The degree of absorption of ammonium nitrate is about 15-20% higher than that of urea. The volatilization degree of the two products is different, with a difference of 15-20% in favour of urea, which at the same time pollutes the air by about 15 t CO2/ha and which leads to the warming of the atmosphere. Starting from here, we consider that ammonium nitrate, although not circumscribed to bioeconomic agriculture, is much closer to it than urea.
Keywords: Q10; Q16; Q57; 330; nitrogen fertilizers; wheat; bioeconomic models; bioeconomic agriculture